Reflection of history in Toni Morrison's beloved - Soofastaei, Elaheh; Kaur, Hardev; Mirenayat, Sayyed Ali (Perpustakaan Sultan Abdul Samad, Universiti Putra Malaysia, 2015)
Slavery as a ruthless possessiveness outlines individuals as their portable possessions,whereas rejecting to identify their distinct identity. Slavery has a very close relationship with slave’s memory. Beloved portrays the emotional response of each character to unimaginable loss and suffering. Masterfully, Toni Morrison tries to show the Negro characters in the history which their traumatic memories are always with them. This paper tries to shed light on the reflection of history on slavery,memory and discourses in this novel in which characters have tragedy to forget their awful memories concerning the Slavery in the United States. In this way, it uses the critical views by Rigney, Mathieson and Fitzgerald.